If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x-5)=2(3x-2)
We move all terms to the left:
7(x-5)-(2(3x-2))=0
We multiply parentheses
7x-(2(3x-2))-35=0
We calculate terms in parentheses: -(2(3x-2)), so:We get rid of parentheses
2(3x-2)
We multiply parentheses
6x-4
Back to the equation:
-(6x-4)
7x-6x+4-35=0
We add all the numbers together, and all the variables
x-31=0
We move all terms containing x to the left, all other terms to the right
x=31
| Q=2u2-5 | | 32=30-2x | | 4-3x=10x-5x | | -39=14x+3=115 | | x-3-2x-37=0 | | 18-2b=6 | | (x+8)^4=0 | | 4x+3= | | 5x^2-20x/20=x/5 | | 5x^2-20x/(20)=x/5 | | W=-3x*4 | | 3x+14=12x+16 | | 2x/5=21/15 | | 9x^+3x+14=12x+16 | | X=2x+11=27 | | x=11+5x=71 | | 4(p–3)=2p+7. | | -22=5p-45 | | P=2Qs+8 | | (3,95xM)+(4,45xS)=102,30 | | 5-t=32 | | 3,95xM+(4,45xS)=102,30 | | 6−(x/3)=3 | | 16-4y/5=16 | | (x/4)-9=13 | | (x/7)+11=15 | | (x/5)-3=8 | | (x/3)+7=9 | | D=j/3+4 | | x=0.345 | | 2x+(-8x)+2=10 | | 7b–8=55 |